Avançar na participação com vistas à transformação: o Movimento Consulta Popular - Wansetto, Rosilene (2009)
Participatory democracy is the subject of numerous studies. In this research, we intend to contribute to renewing the analysis of the topic, highlighting the participatory political action with a view to formulating a popular project to Brazil. The completion of this project requires profound social changes and, therefore, collides with the liberal-democratic model of political representation. For this reason, the search for alternatives to that model is present in the struggles of contemporary social movements, especially in Latin America. Upon analyzing this challenge, we will focus on the perspective of Movimento Consulta Popular MCP